Pengaruh Komunikasi Interpersonal terhadap Kesiapan Kerja Menjadi Guru - Nurjanah, Nunung; Rahmadina, Sonia Aisyah; Chisbiyah, Lismi Animatul; Effendi, Muhammad Idris (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2025)
Based on the phenomenon that occurs in the field, the world of work requires graduates who not only graduate with high grades but also have strong communication skills, honesty and the ability to cooperate with others. Interpersonal communication is needed for work readiness for everyone who will continue in the world of work, especially in the field of education. One of them is teachers, because the interpersonal communication that teachers use tends to produce relationships that are able to influence each other. In general, this study aims to analyze the effect of interpersonal communication on Faculty of Engineering students on work readiness to become teachers. The type of research is quantitative through survey methods and data collection techniques through purposive sampling. The results of hypothesis analysis obtained Sig value. variable X is 0.000 <0.05 and thus the conclusion is Ha accepted and Ho rejected. The results generally found the influence of interpersonal communication (X) on job readiness to become a teacher (Y). Furthermore, the t table is obtained which is worth 2.352 and has a significance of a = 5%. The reference is t count> t table (5.338> 2.352), thus the conclusion is that there is a positive influence of interpersonal communication on job readiness to become a teacher.